Determinan Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM) dalam Upaya Mendukung Banyuwangi sebagai Kota Tujuan Wisata - Achmad Iqbal; Ni Kadek Yuliandari (University of Merdeka Malang, 2019)
This study aims to know the determinants of MSME performance in Banyuwangi. This research is an explanatory research. Samples determining in this study use a purposive sampling technique. Primary data in this study is collected by survey techniques for 51 MSME players in Banyuwangi. This study uses SEM-PLS analysis. The exogenous variables are Market Orientation (MO), Learning Orientation (LO), Innovation (IN), and Technology Orientation (TO). The endogenous variable is the performance of MSMEs. The results of this study show that MO, LO, and TO variables are not the factors that can improve the performance of MSMEs. In other word, the results show that MSME players have not considered MO, LO, and TO in their operations. The results of this study also show that the IN variable are able to improve the performance of MSMEs in Banyuwangi. This means that the higher the innovation carried out by MSME players, the more better the performance of MSMEs in Banyuwangi.https://doi.org/10.26905/jmdk.v7i2.3023